Dynamic Two-Sided Pricing under Sequential Innovation - LIN, Mei (Institutional Knowledge at Singapore Management University, 2013)
Many two-sided platforms offer innovative hardware products that improve in quality and enter the market sequentially. We analyze the impact of the decrease in the production cost on a monopoly platform owner's dynamic two-sided pricing problem, in which buyers are strategic and exert a cross-side network effect to the seller side. Our findings show that a greater decrease in cost raises the optimal price of the low-quality product and allocates more buyer-side demand to the future market. Furthermore, such decrease in cost may also lead to a higher optimal price for the future higher-quality product, given a sufficiently significant quality improvement. Thus, a greater decrease in cost can enable the platform to position its product line to the high-end market. Compared to the base case in which the seller side is absent, we find that, in the two-sided model, the network effect intensifies the impact of cost decrease on the price of the low-quality product and makes the forward intertemporal demand shift on the buyer-side more pronounced. Moreover, the network effect propagates intertemporally, which may reverse the impact of cost decrease on the optimal price of the high-quality product compared to that in the base case, when the quality improvement is less significant. Our work underscores the importance of network effects in a dynamic platform pricing problem and highlights buyers' strategic behavior, production cost, and quality improvements in two-sided pricing.